INTERACTIONS AMONG LEARNING STYLES, LANGUAGE LEARNING STRATEGIES AND GENDER OF EFL LEARNERS - Rizka Nurul Atika (SALEE: Study of Applied Linguistics and English Education, 2020)
Many studies have investigated isolated dimensions of learning styles (e.g. field independence/dependence) for their role in foreign language learning, but relatively few studies have used a comprehensive learning styles instrument to determine predictors of language learning strategies used by students. Hence, employing the descriptive and correlational method, this study aimed to identify students’ minor, major, and negligible learning styles, students’ usage of language learning strategies, the difference in the learning styles and language learning strategies based on gender, and the relationships among those three variables. A total of 30 students enrolling in the first year of senior high school were given two kinds of questionnaire, the Indonesian version of PLSQ and SILL. The result revealed gender differences only occurs in compensation strategy, in favor of female students. Furthermore, the correlational study revealed significant relationships between visual style and cognitive and metacognitive strategies; between auditory style and cognitive and compensation strategies. Moreover, social strategies are correlated with tactile, group, and individual styles. These findings are useful for both teacher and student to employ strategies suitable with their learning styles.